(untitled) (Journal of Hama University, 2024)
Knowledge of the mechanisms and reasons for choosing the preferred host by the wheat stem sawfly leads to the development of effective integrated management techniques for this pest, based on the Trap crop or traps containing materials attracting this pest, with the aim of protecting the desired crop from infection. We conducted a field experiment on barley, as it is the most preferred host compared to the rest of the hosts of this pest in Syria, and three varieties of barley were selected (Furat 1, Furat 5, and Arabi aswad), which were selected from a previous field screening experiment to infect this pest for nine varieties of barley approved as seeds Distributed to farmers in Syria.. wheat stem sawfly females preferred to infect the plants of the variety (Arabi aswad) with significant differences compared to the two varieties (Furat 1 and Furat 5), although there were no significant differences between the preferred variety and the other two varieties in plant height in the early stages of barley’s life coinciding with the spread of the wheat stem sawfly, or The slower development of its plants in the late stages of barley’s life coincides with the spread of wheat stem sawfly. Therefore, we analyzed and identified volatile plant compounds using GC-MS technology and compared them with the results of international research in this field The leaves of the preferred variety (Arabi aswad) were distinguished compared to the two varieties (Firat 1 and Firat 5) by containing a higher percentage of the compound (6-methyl-5-hepten-2-one), which attracts the wheat stem sawfly females (Cepus cinctus), as well as the volatile organic plant organic compound, the monoterpene Neral (citral), which Its oxidation products (acetic acid and formic acid) attract the citrus psylla insect, Diaphorina citri. In contrast, the concentration of linalool and its derivatives (Cis-Linalool oxide) in the leaves of the preferred variety (Arabi aswad) was lower than in the leaves of the two varieties (Firat 1 and Firat 5), which is the well-known compound With its repellent effect on Herbivores insects.